2017
DOI: 10.1186/s13047-017-0201-x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral wedges with and without custom arch support for people with medial knee osteoarthritis and pronated feet: an exploratory randomized crossover study

Abstract: BackgroundPronated foot posture is associated with many clinical and biomechanical outcomes unique to medial compartment knee osteoarthritis (OA). Though shoe-worn insole treatment, including lateral wedges, is commonly studied in this patient population, their effects on the specific subgroup of people with medial knee OA and concomitant pronated feet are unknown. The purpose of this study was to evaluate whether lateral wedge insoles with custom arch support are more beneficial than lateral wedge insoles alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
0
24
0
2
Order By: Relevance
“…Mean±SD of external knee adduction moment at early, mid, and late stance in 3 conditions: without insole, lateral wedge insole, and lateral wedge insole and a subtalar strap (n =17). 5 support ended to a protracted controversy (7,13,14,31). The possible explanations could be related to the variation among the sample of the studies or the interventions used in the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean±SD of external knee adduction moment at early, mid, and late stance in 3 conditions: without insole, lateral wedge insole, and lateral wedge insole and a subtalar strap (n =17). 5 support ended to a protracted controversy (7,13,14,31). The possible explanations could be related to the variation among the sample of the studies or the interventions used in the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fixing the talus movement with a subtalar strap may increase the valgus angulation of the talus and augment the femorotibial angle change (11,12). Moreover, the effect of LWI can be increased if it is joined with the foot comfort, which is associated with concomitant use of longitudinal arch support (13,14). Although the augmented effect of LWI and a subtalar strap have been shown by reducing EKAM in KOA, the impact of using LWI with an arch support and a subtalar strap in reduction of EKAM has not yet been known (11,12).…”
mentioning
confidence: 99%
“…In the experimental shoes, the midsole was stiffer (ie, firmer) on foot‐ground contact because of the addition of the plastic tubes. Secondly, the medially posted shoe (Condition 2) could result in less eversion during the support period, while the laterally posted shoe (Condition 3) may result in greater eversion …”
Section: Methodsmentioning
confidence: 99%
“…In contrast, several problems related to the foot, such as flatfoot and pronated foot, have been reported in KOA. 13,14 The change in the shape of the foot in KOA may cause pain, restriction of the daily activities, and damage to the articular cartilage. [14][15][16] Since the movement of the foot has a close relationship with the tibia, the effect on the knee joint is marked, 17 and it is reported that the pronated moment of the subtalar joint during walking simulation increases due to the varus deformity of the knee joint.…”
Section: Introductionmentioning
confidence: 99%